Política de acessibilidade às pessoas com deficiência na educação superior: desdobramentos jurídicos - Scott Junior, Valmor (2012)
This research aims to understand what is being produced on the accessibility for individuals with disabilities in higher education of Universidade Federal de Santa Maria UFSM, in the period 2007 to 2010, in the official documents submitted by federal prosecutors (MPF) to UFSM and what it was answered by that educational institution. Given this, it is proposed to qualitative research, being used content analysis as methodology. The official referrals were analyzed from three categories: legal developments, university environment and accessibility in relation to MPF and UFSM. The questions that guided this study sought to understand, basically, what these documents have on accessibility policy in the academic context, particularly the speech of each of the institutions (MPF and UFSM). To familiarize the reader in analyzing the results and discussion were elaborated three theoretical chapters, the first being: The Brazilian constitution and the processes of in-exclusion, with the lifting of the processes of inclusion and exclusion in the constitutions of Brazil, in collaboration with Alves; Barbosa, 2006; Cury, 2005; Duarte, 2004; Fávero, 2007; Marquezan, 2009; Mazzotta, 2005; Pinto, 1999; Pieczkowski, 2011; Santos, 2009; Teixeira, 2008; Veiga Neto, 2001, and others. The second chapter: Accessibility policy in the context of UFSM presents the institution context and its policy of accessibility, with the support of Castro, 2010; Cruz; Dias, 2009; Glat; Blanco, 2007; Guerreiro; Almeida, 2010; Moreira, 2006; Pereira, 2006; Sassaki, 2005; Watzlawick, 2009, and others, and finally, the chapter: The education and their protection by federal prosecutors that displays the MPF, its role as guarantor of the right to education and tools to enforce this guarantee, with Boaventura, 2005; Chizotti, 2005; Lima, 2007; Silveira, 2007; Oliveira, 1995; Tessmann; Sangoi, 2009, and others. The results indicate the production of the accessibility for the MPF, the architectural bias, based on the discourse of Law and UFSM, for carrying out communication actions, attitudes and pedagogic.